Źródła zanieczyszczeń rzeki Warty = The pollution source of Warta river - Lewandowski, Piotr; Szustakowski, Mieczysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Warta river flows in central part through developed economically region of Poland. On base of magnitude of drops of sewage on investigated section of Warta river, so-called equivalent density of population (EDP) of examined catchment was counted.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)